Carotid artery stenting. Issue 5 (9th August 2013) - White, Christopher J.; Ramee, Stephen R.; Collins, Tyrone J.; Jenkins, J. Stephen; Reilly, John P.; Patel, Rajan A. G.
<x xml:space="preserve">Abstract</x> From the earliest experiences with carotid artery stenting (CAS) presumptive high risk features have included thrombus‐containing lesions, heavily calcified lesions, very tortuous vessels, and near occlusions. In addition patients have been routinely excluded from CAS trials if they have contra‐indications to dual antiplatelet therapy (aspirin and thienopyridines), a history of bleeding complications and severe peripheral arterial disease (PAD) making femoral artery vascular access difficult. Variables that increase the risk of CAS complications can be attributed to patient characteristics, anatomic or lesion features, and procedural factors. Clinical features such as older age (≥80 years), decreased cerebral reserve (dementia, multiple prior strokes, or intracranial microangiopathy) and angiographic characteristics such as excessive tortuosity (more than two 90° bends within 5 cm of the target lesion) and heavy calcification (concentric calcification ≥ 3 mm in width) have been associated with increased CAS complications. Other high risk CAS features include those that prolong catheter or guide wire manipulation in the aortic arch, make crossing a carotid stenosis more difficult, decrease the likelihood of successful deployment or retrieval of an embolic protection device (EPD), or make stent delivery or placement more difficult. Procedure volume for the operator and the catheterization laboratory team are critical elements in reducing the risk of the procedure. In this article, we help CAS operators better understand procedure risk to allow more intelligent case selection, further improving the outcomes of this emerging procedure.© 2013 Wiley Periodicals, Inc.